IMPLEMENTASI STANDAR NASIONAL PERPUSTAKAAN PERGURUAN TINGGI DI UNIVERSITAS RIAU TAHUN 2018-2019 - Fauziana Ulfi; Wazni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The quality of college is in line with the quality of its library. Riau University continues to strive for improve the quality of its library. Riau University Libraries has received Accreditation A in 2013 and is getting it again accreditation A in December 2019. In addition, Riau University Library as well received ISO 9001: 2008 in 2018 and updated to ISO 9001: 2015 in 2019. However, with accreditation A said, Riau University Library still does not comply with the Head's Regulation National Library No. 13 of 2017 concerning National Standards for College Libraries. This study aims to describe (1) implementation of the National Standards for College Libraries at the University Riau in 2018-2019 and (2) factors affecting the implementation of the National Standard for College Libraries at Riau University in 2018-2019. The research method used is qualitative descriptive research type. Research location at Riau University Library. Sources of data in this study are informants, mass media and documents. The data collection technique through  documentation and interviews. The results of this study indicate that the implementation of the National Standard for College Libraries at Riau University in 2018-2019 is not optimal yet. There are several indicators that have not been fulfilled in these standards, such as the number of book and magazine collections that are still lacking, additional collections in a year less than 3% of the total collection existing, building area not up to standards, unqualified library staff standard, and the total budget which is only 0,8% of the total budget of Riau University. Based on Edward III's theory of Policy Implementation, communication, disposition and organizational structure has been achieved. However the resource  factor has not yet been achieved. This causes the lack of student’s interest to visit UNRI library. The number of visitors to the UNRI Library is not comparable with the number of students at the University of Riau. Average number of visitors Riau University Libraries in 2018 as many as 5,200 people and in 2019 as many as 4,169 people. Meanwhile, the number of students at Riau University that year about 35,000 people.Keyword: Implementation, National Standards for Libraries